2009
DOI: 10.1002/lapl.200910048
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable continuous wave mid-IR DFG source based on fiber lasers and amplifiers

Abstract: Abstract:In this paper we report a fiber-type widely tunable CW mid-IR DFG/QPM laser source based on periodically poled MgO-doped LiNbO 3 (PPMgLN), which uses a ytterbium-dope fiber laser (YDFL) as the pump source and a tunable erbium-dope fiber laser (EDFL) cascaded with an erbium-doped fiber amplifier (EDFA) as the signal source. Our experimental results show that, with the PCs to adjust the pump and signal polarization orientations being parallel to the crystal principle optical axis the conversion efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The main advantages of frequency conversionbased mid-IR laser sources are wide, non-complex tuning, narrow line width and in most cases, a modular structure. The designs most commonly found in the literature use fiber based lasers [7,8] or solid state lasers [9]. Fiber based DFG mid-IR sources have a simplified design with a minimal number of bulk optical elements used in the setup.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of frequency conversionbased mid-IR laser sources are wide, non-complex tuning, narrow line width and in most cases, a modular structure. The designs most commonly found in the literature use fiber based lasers [7,8] or solid state lasers [9]. Fiber based DFG mid-IR sources have a simplified design with a minimal number of bulk optical elements used in the setup.…”
Section: Introductionmentioning
confidence: 99%
“…Høgstedt et al demonstrated a tunable CW DFG source with 3.06-mW maximum power at 3.03 μm [3]. Their 500 nm tuning range resulted from shifts between four different grating periods together with adjustments of crystal [16]. This wavelength range is attractive for the detection of several species through the H-C stretch vibration and fortuitously, can be reached by DFG between 1 -1.1 μm and 1.5 -1.6 μm, where excellent fiber-based sources have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Erbium-doped fiber lasers (EDFLs) and other doped fiber lasers can be used for gas detection, since they are able to operate over a large wavelength range [15,16], including absorption lines of several important gases, e.g., C 2 H 2 , CO, CO 2 , NO, OH, HCN, and HI [17]. The recently reported Bi-doped fiber laser and optical amplifier [18] have a wide spectral region from 1150 to 1550 nm, covering more gases of interest.…”
Section: Introductionmentioning
confidence: 99%